A study of the effects on the ovarian cycle of athletic training in different sports - Sambanis, M.; Kofotolis, N.; Kalogeropoulou, E. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: The purpose of this research was to investigate the effects of sports training on the ovarian cycle of athletes of various disciplines, and of non-athletes, their participation and their performance in competition as well as the appearance of symptoms of discomfort pre and during the duration of menstruation. Methods: Athletes from the disciplines of basketball, track athletics, gymnastics, swimming, synchronized swimming and water polo as well as non-athletes took part in this research. All the participants, both athletes and non-athletes were selected and completed a specially designed questionnaire. Results: The results of the research showed that there are no significant differences in the menarche to the duration of the ovarian cycle and to the duration of the menstrual flow. Also, the involvement in different athletic disciplines appears to affect to different degrees the regularity of the cycle although this does not prevent the athlete from participating in training and in competition. The effects are sometimes beneficial to their performance and sometimes they could have a negative effect on their performance. Regarding the symptoms and the discomforts which occasionally appeared pre and during the duration of menstruation e.g. headache symptoms, these appear to be greatly decreased in the athletes of swimming, synchronized swimming and water polo and perhaps this is a result of the beneficial effects of the water. The percentage for abdominal pain appeared decreased for certain disciplines (such as swimming) or stable both pre and during the duration of menstruation. Concerning the pain in the thoracicolumbar region, the percentages were different for every sport: a noticeable decrease was recorded for the athletes of swimming, gymnasts, synchronized swimming, water polo, track athletes and the non-athletes, but with an increase for the basketball players. For the symptoms of weakness and fatigue, the percentages were increased for all the athletic disciplines as well as for the non-athletic during the duration of menstruation compared with pre menstruation, although for the percentages for symptoms of nervousness, the picture was different, that is, the percentages appeared decreased during the duration of menstruation. Conclusion: In conclusion, where problems appear in the function of the ovarian cycle, the assistance of a specialist gynaecologist is considered essential when we are sure that these problems are not caused by training, malnutrition or psychological factors.